Social Media on Islamic Lifestyle Trends: A Systematic Literature Review - Eva Anzani Siregar; Mufida Tullaili; Zul Afdal (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the rapid development of social media, so it is necessary to explore the role of social media in influencing Islamic lifestyle trends among young Muslim consumers, focusing on the role of influencers, content platforms, and their impact on religious identity. This study uses a systematic literature review (SLR) with the PRISMA method using data from 2020 to 2024 on how social media influences the adoption of Islamic lifestyle trends by young Muslims. The research findings show that social media platforms are key in shaping the religious and cultural identities of young Muslims, with influencers playing an important role in promoting Islamic values ​​and encouraging consumption behavior that is in line with halal principles.